Advising the Student-Athlete - Gurney, Gerald S.; Johnston, Sally P. (My University, 1986)
The purpose of this essay is to review recent institutional studies which describe the academic preparation and subsequent performance of student-athletes and to discuss their implication for the advising process. This was a reprint from a NACADA Journal article.
Keywords: academic support; stereotypes